Differences in Parathyroid Hormone-Related Peptide and Serum Electrolytes in Acute Leukemia Patients - Damar Sulistyantoko; Maria Immakulata Diah Pramudianti; Dian Ariningrum (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
Acute leukemia is a clonal malignancy of myeloid or lymphoid precursor cells. Parathyroid hormone-related protein (PTHrp) is an 84 amino acid protein released by the parathyroid glands. Serum electrolyte disturbances are common in acute leukemia patients. This study aimed to determine the difference in the levels of PTHrp and serum electrolytes (sodium, potassium, calcium ion) in acute leukemia patients. An observational analytic research, cross-sectional approach was performed at the Dr. Moewardi Hospital in Surakarta between June and August 2019 with 43 subjects. Acute leukemia, based on the FAB classification, is divided into two groups (myeloid and lymphoid lineage). The serum was used for measurement of PTHrp levels with enzyme immunoassay (ELISA) principle (the Rayto RT-2100C) and serum electrolyte with the Ion Selective Electrode (ISE) method (AVL analyzer). The data were tested by comparison test and ROC curve, p was significant if <0.05, and the confidence interval was 95%. Acute leukemia subjects comprised 24 lymphoid lineages (55.8%) and 19 (44.2%) myeloid lineages subjects. The mean age was 25 (7-47) years, with 18 (41.9%) male subjects and 25 (58.1%) female subjects. The mean sodium level was 136 (132-140) mmol/L, with a mean level of 134.38±4.75 mmol/L and 137.00 (121-143) mmol/L in the lymphoid and myeloid lineage groups, respectively. The cut-off point for serum sodium levels was 135.5 mmol/L, with an AUC of 0.679, a sensitivity of 73.7%, and a specificity of 67.7%. There was a significant difference in serum sodium electrolyte levels in acute leukemia patients (p=0.046) but not in acute leukemia patients' serum potassium, calcium ion, and PTHrp levels (p=0.415; p=0.912 and p=0.293, respectively). Further research was needed in the chronic leukemia population and other research variables related to electrolyte balance.